Acute effect of spinal cord stimulation on autonomic nervous system function in patients with heart failure - Naar, Jan; Jaye, Deborah; Neuzil, Petr; Doskar, Petr; Malek, Filip; Linderoth, Bengt; Lind, Goran; Stahlberg, Marcus (Journal of applied biomedicine, 2021)
AIMS: To test the hypothesis that spinal cord stimulation (SCS) acutely improves heart rate variability (HRV) and baroreceptor sensitivity (BRS) in patients with heart failure (HF). METHODS: SCS (15 minutes) was delivered in four different settings: 90% of maximal tolerated stimulation amplitude (MTA) targeting the T1-T4 spinal cord segments (SCS90T1-4), 60% of MTA (SCS60T1-4), 90% of MTA with cranial (SCS90CR) and caudal (SCS90CA) electrode configuration. HRV and BRS were recorded continuously and stimulation was compared to device off. RESULTS: Fifteen HF patients were included. SCS90T1-4 did not change the standard deviation of intervals between normal beats (SDNN, p = 0.90), BRS (p = 0.55) or other HRV parameters. In patients with baseline SDNN <50 ms, SCS90T1-4 significantly increased SDNN (p = 0.004). CONCLUSIONS: Acute SCS at 60-90% of MTA targeting upper thoracic spinal cord segments does not improve autonomic balance or baroreceptor sensitivity in unselected patients with heart failure but may improve HRV in patients with low SDNN.
Keywords: autonomní nervový systém; Spinal Cord Stimulation; míšní stimulace; Heart rate variability; Heart Rate; Spinal cord stimulation; Humans; Autonomic Nervous System; Heart failure; Heart Failure; lidé; srdeční selhání; srdeční frekvence; Baroreceptor sensitivity